Hepatitis B vs. hepatitis C infection on viral hepatitis-associated hepatocellular carcinoma - Hiotis, Spiros; Rahbari, Nuh Nabi (BMC gastroenterology, 2012)
To determine clinical-pathologic variables in patients with a new diagnosis of hepatocellular carcinoma (HCC) and underlying hepatitis B vs. C infection.